GAMBARAN SISTEM PENYELENGGARAAN MAKANAN DI PONDOK PESANTREN, KABUPATEN JEMBER - Farida Wahyu Ningtyias; Irma Prasetyowati; Ida Srisurani Wiji Astuti; Siti Muslicha; Ahmad Nafi'; Ahmad Haryono (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2018)
The good procurement of the food in a boarding school has guarantee the nutritional needs of the students. This study aims to describe the implementation of the food in the boarding school in the district of Jember. This type of research is qualitative research with descriptive approach using primary and secondary data. The informant in this study is the executive management of the boarding school and the cheff manager. The Processing and analyzing of data is using content analysis and presented in narrative form and quote. The results showed a third implementation of the boarding school was a self-managed non-commercial. The executive manager was Ning (daughter of the owner of boarding school) or coordinator of ustadzah (teacher). Only NI boarding school that has a menu cycle i.e 10 days cycle menu, budget planning is done by those responsible for food manager and Ndalem (family members of the owner of boarding house). Purchases made directly groceries every day, which storage was FIFO. Food preparation is done two times, in the morning hours of 6:00 pm and 15:00 pm. There was no calculation for nutritional adequacy andthe students consumption were still in the deficit category. Food procurement in a boarding school need to increase with planning optimizing,